El proceso de lectura en lengua extranjera: de la descodificación a la interpretación - Ruiz Cecilia, Raúl (Didáctica. Lengua y Literatura, 2010)
In the last decades, the reading process has been strongly supported by the advances in the field of psychology and psycholinguistics. Thus, instead of analyzing reading just concentrating on the outcomes, no mattering how we had reached the final interpretation, theorists have opted to prioritize the cognitive processes which give control to the reader over the text. This leads me to support the thesis that there are not two readers who may respond identically to the written text. This paper focuses on the different stages that an EFL student should overcome to apprehend a text. In addition, it also draws attention to how the reader’s response will vary depending on several factors such as linguistic competence, cultural competence, meaningfulness of the text, motivation…
Keywords: Foreign language; Reading; Reading process; Interpretation